Prescribing antibiotics to pediatric dengue: increasing risk of bacterial resistance - Dhanunjaya Sandopa; Sree Keerthi Nethi; Sai Charitha Sreeram; Narasimha Kumar Godlaveti Vijay; Vyshnavi Biradavolu; Jagadeesh Vijay Kakimani (Indonesian Pediatric Society, 2018)
Background Use of antibiotics to treat self-limiting viral infections like dengue fever (DF) without any co-morbid conditions in pediatric patients is common practice in India, and a major contribution of the inappropriate use of antibiotics in the country. Objective To provide an analysis of diagnosis, grading, and prescribing of antibiotics in pediatric inpatients with DF in a tertiary care teaching hospital in India. Methods Data from case sheets of all pediatric inpatients (n=370) diagnosed with DF without co-morbid conditions were collected with regards to diagnosis, grading, presence, and appropriateness of antibiotic usage according to the 2009 WHO Guidelines, the National Vector Borne Disease Control Program (NVBDCP) of India Guidelines, and the Hospital Infection Society (HIS) Guidelines. Results Platelet count determination (50% of the cases) was the major diagnostic method for dengue. Inappropriate grading of DF was seen in 20% of patients. Almost 75% of the 370 dengue cases were prescribed antibiotics for the expressed purpose of avoiding hospital-acquired infections. A single antibiotic was given in 225 cases (60.81%), 2 antibiotics in 33 (8.91 %) cases, and 3 antibiotics in 9 (2.43%) cases. Conclusions From the results it is clear that antibiotics were prescribed to treat DF where the antibiotics do not have any role. DF is a self-limiting viral infection that can be treated with proper management of hemodynamic status with IV fluids. To avoid the usage of antibiotics in the treatment of dengue, awareness has to be created in healthcare professionals regarding the treatment guidelines for dengue and appropriate use of antibiotics to avoid hospital acquired infections.